ANALYSIS OF THE PRESENT STATE OF THE TRANSPORT COMPLEX OF RUSSIA - D. Abdyusheva (Вестник университета)
The current state of the transport system in Russia based on the data of the Federal State Statistics Service has been analyzed. Russia in gures - 2017, which presents the main indicators of transport. The dynamics of these basic indicators of the transport system of the Russian Federation is outlined, current trends and future development plans are reected. The analysis analyzed by the author is assessed as the basis for assessing the prospects for the development of the transport system of the Russian Federation. Recommendations for improving the transport complex of Russia are given.